How do you multiply (2x - 5) ( 6x ^ { 2} - 6x - 11)?

1 Answer
May 1, 2018

12x^3-42x^2+8x+55

Explanation:

Simply multiply each term in each bracket, but not terms in the same bracket.

(color(red)(2x)color(blue)(-5))(color(green)(6x^2)color(red)(-6x)color(blue)(-11))

color(red)(2x) xx color(green)(6x^2)=color(orange)(12x^3)

color(red)(2x) xx color(red)(-6x)=color(green)(-12x^2)

color(red)(2x) xx color(blue)(-11)=color(red)(-22x)

color(blue)(-5) xx color(green)(6x^2)=color(green)(-30x^3)

color(blue)(-5) xx color(red)(-6x)=color(red)(30x)

color(blue)(-5) xx color(blue)(-11)=color(blue)(55)

Collect like terms:

color(orange)(12x^3)color(green)(-12x^2-30x^2)color(red)(-22x+30x)color(blue)(+55)

rArr color(orange)(12x^3)color(green)(-42x^2)color(red)(+8x)color(blue)(+55)

rArr 12x^3-42x^2+8x+55